Assisting pregnant mothers with NLP affirmation method for childbirth preparation in a complementary school - Florentina Kusyanti; Lestariningsih Lestariningsih; Leni Leni; Anisah Anisah (Universitas Muhammadiyah Magelang, 2024)
Pregnancy is a psychologically vulnerable phase, during which pregnant women are prone to stress and emotional changes. Therefore, structured support from the first to the third trimester is essential. The